2013
DOI: 10.1177/0148607113482000
|View full text |Cite
|
Sign up to set email alerts
|

Care Coordination to Enhance Management of Long‐Term Enteral Tube Feeding

Abstract: Studies suggested a positive association of care coordination by a multidisciplinary team approach and improved patient outcomes for long-term enteral feeding patients. However, the available evidence does not allow estimating the effectiveness of a particular intervention or team composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 34 publications
(30 reference statements)
1
47
0
5
Order By: Relevance
“…Advance practice nurse care [136], quality improvement strategies [137, 148152], case management [138], collaborative care [140], evidence-based medicine practice strategies [144], midwife-led continuity services [145], comprehensive asthma care [146], and patient-centered medical home [125, 147] have all been evaluated. Moderate- to high-quality reviews demonstrated improved safety, quality care, increased vaccination rate, and improved management of patient with depression and anxiety in primary healthcare settings [135137, 139142, 144, 147, 148, 150, 151]. Few reviews failed to provide any conclusive outcomes [122, 126, 129, 131, 134, 143, 154, 155].…”
Section: Resultsmentioning
confidence: 99%
“…Advance practice nurse care [136], quality improvement strategies [137, 148152], case management [138], collaborative care [140], evidence-based medicine practice strategies [144], midwife-led continuity services [145], comprehensive asthma care [146], and patient-centered medical home [125, 147] have all been evaluated. Moderate- to high-quality reviews demonstrated improved safety, quality care, increased vaccination rate, and improved management of patient with depression and anxiety in primary healthcare settings [135137, 139142, 144, 147, 148, 150, 151]. Few reviews failed to provide any conclusive outcomes [122, 126, 129, 131, 134, 143, 154, 155].…”
Section: Resultsmentioning
confidence: 99%
“…Essential components of the education process include training on feeding tube and access site care, preparation and administration of formula, medication administration, enteral pump operation, monitoring and troubleshooting complications, and emergency care plan and contact information 6 , 8 . ‐ 12 Thompson et al 13 have emphasized the need for clinicians to evaluate the effectiveness of their EN education process, provide comprehensive EN education and patient resources, proceed over more than 1 educational session, and prepare patients and caregivers to resolve foreseeable problems, such as tube occlusion and dislodgement, skin care issues, and psychosocial challenges.…”
Section: Section 11 Transition Of Carementioning
confidence: 99%
“…Enteral nutrition is a safe and cost-effective intervention to feed patients who cannot cover all requirements from food or oral nutritional supplements, or who cannot swallow safely (9).…”
Section: Discussionmentioning
confidence: 99%
“…Enteral nutrition (EN) has been found to be beneficial in patients with a wide range of conditions, including burns, chronic obstructive pulmonary disease, gastrointestinal surgery or liver diseases (7,8). In addition, it has been shown to be safe and cost-effective and, since its introduction, it has become an established procedure (9).…”
Section: Introductionmentioning
confidence: 99%